The Effect of Seasonal Groundwater Level Rise on the Zeleny Value of Winter Wheat - Kerezsi, György; Waltner, István; Géczi, Gábor (Journal of Central European Green Innovation, 2025)
The topic of the research is to examine the effect of temporary waterlogging on winter wheat under controlled, lysimeter conditions. The aim was to analyze plant responses specifically yield and the Zeleny value at different water levels of 0 cm (two-phase soil), −30 cm (water level set at 30 cm below the surface), and −60 cm (water level set at 60 cm below the surface) and durations (3, 6, 9, 12 days). The statistical methods used MANOVA, ANOVA, Welch’s test, the Games-Howell post-hoc test, and multivariate correlation helped map significant differences in the results. The Pearson correlation matrix confirmed a highly significant, strong positive correlation between the quality indicators (r = 0,955-0,989, p < 0,001), whereas yield showed a weak positive correlation with the quality parameter (r = 0,155). According to the Games-Howell post-hoc tests, for the Zeleny value, moderate stress particularly the 9-day treatment at a −60 cm water level significantly improved quality (e.g., 2021, −60 cm, 9 days vs. 3 and 6 days: p = 0,031 and p = 0,004). Under the same conditions (e.g., 2021, −60 cm, 9 days), yield did not differ significantly from the control according to Welch’s t-test (p = 0,4032). Quality improvement is not necessarily associated with yield increase; indeed, in other cases yield may even decrease. In 2021, at the 0 cm water level, the 6-day treatment significantly reduced yield (p = 0,0496), while the 9- and 12-day treatments increased it (p = 0,009, p = 0,034). Zeleny value: in 2020 at −60 cm, the continuous treatment was significantly worse than the 12-day treatment (p = 0,004), whereas in 2019 at the same water depth, the continuous treatment was significantly better than the 3-day treatment (p < 0,0001). For yield, in 2021 at −60 cm, continuous flooding resulted in a significantly lower yield than the 12-day treatment (p = 0,005). Conversely, in 2020 at −60 cm, the continuous treatment was significantly better than the 3-day (p = 0,026) and 9-day (p = 0,003) treatments. This pattern underscores the risky and year-specific nature of continuous treatment.